The impact of wildfires on the diet of Podarcis lusitanicus revealed by DNA metabarcoding - Catarina Simões; Diana S. Vasconcelos; Raquel Xavier; Xavier Santos; Catarina Rato; D. James Harris (PLoS ONE, 2025)
Fire has long been recognized as an important ecological and evolutionary force in plant communities, but its influence on vertebrate community ecology, particularly regarding predator-prey interactions, remains understudied. This study reveals the impact of wildfires on the diet of Podarcis lusitanicus, a lizard species inhabiting a fire-prone region in the Iberian Peninsula. In order to explore diet variability associated with different local burn histories, we evaluated P. lusitanicus diet across three types of sites in Northern Portugal: those had not burned since 2016, those burned in 2016, and those more recently burned in 2022. Podarcis lusitanicus is a generalist arthropod predator with dietary flexibility. Given the turnover of arthropod species after fire, it is expected to find variations in diet caused by different fire histories, especially between unburned and recently burned sites. From DNA metabarcoding of faecal samples, our study revealed that while prey richness remained unaffected by wildfire regime, significant shifts occurred in diet composition between more recently burned and unburned areas. Specifically, we found that differences in diet composition between these two fire regimes were due to the presence of Tapinoma ants and jumping spiders (Salticus scenicus). These prey were present in the diets of lizards occupying unburned areas, while these were absent in areas burned in 2022. Interestingly, diets in unburned areas and areas burned in 2016 showed no significant differences, highlighting the lizards’ ecological flexibility and the habitat’s resilience over time. The ant species T. topitotum was found in dominance in both burned areas, suggesting that this species may be fire tolerant. In addition, families such as Cicadellidae and Noctuidae were found to be more associated with more recently burned areas. The use of DNA metabarcoding in this study was essential to provide a more detailed and accurate view of predator-prey interactions in ecosystems susceptible to fire, and therefore a better understanding of changes in prey consumption in this fire-adapted ecosystem.